A Promising Alternative for Sustainable and Highly Efficient Solar‐Driven Deuterium Evolution at Room Temperature by Photocatalytic D2O Splitting. Issue 11 (12th May 2020) - Zeng, Gongchang; Zeng, Heping; Niu, Lishan; Chen, Jiayi; Song, Ting; Zhang, Piyong; Wu, Yixiao; Xiao, Xinyan; Zhang, Yongqing; Huang, Shaobin
Abstract: Motivated by energy shortages and in view of current efforts to develop clean, renewable energy sources based on fusion, a solar‐driven strategy has been developed for deuterium evolution. Deuterium is a critical resource for many aspects. However, the limited natural abundance of deuterium and the complexity of established technologies, such as quantum sieving (QS) for deuterium production under extreme conditions, pose challenges. The new method has the potential for robust and sustainable deuterium evolution, enabling deuterium production at a high rate of 9.745 mmol g −1  h −1 . The activity, thermodynamic, and kinetic characteristics are also investigated and compared between photocatalytic heavy water (D2 O) splitting and water (H2 O) splitting. This study opens a new avenue to discover promising photocatalytic deuterium generation systems for advanced solar energy utilization and deuterium enrichment. Abstract : D‐lightful : A conceptual breakthrough for the combination of efficient deuterium production and recycling of contaminated D2 O by solar‐driven photocatalytic strategy. The new method has the potential for robust and sustainable deuterium evolution, enabling deuterium production at a high rate of 9.745 mmol g −1  h −1 .